2017
DOI: 10.1007/s00359-017-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

How bumblebees use lateral and ventral optic flow cues for position control in environments of different proximity

Abstract: Flying insects frequently navigate through environments of different complexity. In this study, buff-tailed bumblebees (Bombus terrestris L.) were trained to fly along tunnels of different widths, from 60 to 240 cm. In tunnel widths of 60 and 120 cm, bumblebees control their lateral position by balancing the magnitude of translational optic flow experienced in the lateral visual field of each eye. In wider tunnels, bumblebees use translational optic flow cues in the ventral visual field to control their latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…We refer to the blue circle as the target and to the pink-and-white pattern as the background. The chequerboard pattern was necessary for the bees to stabilize their flight Linander et al, 2017 . An Eppendorf tube cap mounted on a transparent acrylic sheet (60 × 80 mm) was filled with syrup and placed over the target.…”
Section: Methodsmentioning
confidence: 99%
“…We refer to the blue circle as the target and to the pink-and-white pattern as the background. The chequerboard pattern was necessary for the bees to stabilize their flight Linander et al, 2017 . An Eppendorf tube cap mounted on a transparent acrylic sheet (60 × 80 mm) was filled with syrup and placed over the target.…”
Section: Methodsmentioning
confidence: 99%
“…2 g). Altogether, these results suggest that ventral optic flow is important for bees to conduct well-controlled flights, both when cruising towards a food source (Baird et al 2006 ; Portelli et al 2010 ; Linander et al 2016 , 2017 ) as well as while performing learning flights.…”
Section: Discussionmentioning
confidence: 87%
“…Previous work in different insects has shown that the texture presented in the ventral and lateral field of view is important for flight control (Linander et al 2017 , 2018 ; Portelli et al 2011 ; Straw et al 2010 ). Our results suggest that it would be interesting to do similar experiments in Episyrphys hoverflies, by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We took photos of the ground over which the hoverfly was performing its behavior and panoramic photographs of the surrounding. We focused on images from the ventral and lateral parts of the visual field as these appear to be particularly important for insect flight control (Linander et al 2017 ; 2018 ; Portelli et al 2011 ; Straw et al 2010 ). In addition, panoramic images have been used extensively to understand motion vision coding in the insect brain (for hoverfly examples, see e.g., O’Carroll et al 2011 , 2012 ; Barnett et al 2010 ; Straw et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%